Ethics and Accountability in Government Bureaucracy - Ousu Mendy (Pancasila and Law Review, 2023)
In recent years, the issues of ethics and accountability within government bureaucracies have remained both contentious and highly relevant to governance. This research offers a comprehensive analysis of the role of ethics and accountability in these bureaucracies, with a particular focus on transparency. Using a normative research methodology and secondary data collection, the research draws on literature such as books, journals, and theses to clarify the current and prevailing conditions within government bureaucracies. The findings indicate that accountability among government bureaucrats can be effectively achieved by imposing multiple and dynamic obligations on both administrators and lower-level bureaucrats. Furthermore, the research suggests that ethics can often be more significant than the law itself, as ethical principles motivate individuals to act morally based on what is right, whereas the law deters behavior primarily through the threat of penalties.